Signaling in Takeover Auctions with Flexible Reserve Price. (8th August 2014) - Khoroshilov, Yuri
Abstract : This paper develops a model of takeover auctions with a two‐step information acquisition process. It shows that the threat of extra information acquisition allows the existence of the signaling jump‐bidding equilibrium even when the seller is able to change its reserve price on the basis of the bidding history. The paper shows that although a higher cost of the secondary information leads to a higher expected price, the precision of the preliminary information has an ambiguous effect on the target's expected profit and that such an effect depends on the number of potential acquirers. Copyright © 2014 John Wiley & Sons, Ltd.